THE EFFECT OF AERATION ON BABY KAILAN (Brassica oleraceae var. Achepala) GROWTH IN FLOATING SYSTEM OF HYDROPONIC TECHNOLOGY INSIDE AND OUTSIDE THE GREENHOUSE - Dian Krisnawati; Sugeng Triyono; M. Zen Kadir (The University of Lampung, 2014)
This research is aimed to find out the effects of aeration on baby kailan (Brassica oleraceae var. Achepala ) infloating systemhidroponic technology inside and outside the greenhouse. This research used a factorial in a splitplot design with 2 factors, namely factor I (weation) and Factor II (aeration). The first factor had two levels,inside (N0) and outside (N1) greenhouse. The second factor consisted of 3 levels; mechanical aeration (A1),hanging styrofoam (A2) and floating styrofoam (A3); resulting in six treatment combinations with threereplications. The data was analyzed using ANOVA (analysis of variance) at 5%significant level and folowed byLSD. The results showed that the inside and otsutside greenhouse significantly affected growth and yield. The useof aeration outside the greenhouse had shownmaximal production. The hanging styrofoamsystem (A2) insidethe greenhouse showed the lowest production cost (fertilizer and electricity. None of the environment andnutrition parameters (EC, DO and pH) was significantly different during the research, implying that theenvironment and nutrion solutionwere homogeneous and did not affect the plant growth.